An innovative chitosan-coated aquatic feed pellets production from coastal waste using top-spray fluidized bed drying - Jatuphat Maikaew; Naruebodee Srisang; Supreeda Tambunlertchai; Siriwan Srisang (Scientific Reports, 2026)
Coastal wastes such as crab shells, shrimp shells, and seaweed are rich in proteins, lipids, and bioactive compounds, making them valuable raw materials for aquafeed production. In this work, three aquatic feed pellets were developed and tested under different drying temperatures from 70 to 110 °C to evaluate the pellet durability index (PDI), specific energy consumption in water removal (SEW), and nutrient quality. The formulation containing high crab shell content showed the most balanced nutritional profile but required further improvement in mechanical strength. To address this, chitosan coating was applied using a top-spray fluidized bed system, with process conditions optimized through response surface methodology (RSM). The RSM demonstrated the optimal coating condition at a concentration of about 1.25% (w/v), a spray rate of about 32.5 mL/min, and a temperature of about 110 °C, with the lowest of drying time (DT) and specific energy consumption (SEC). The optimized coating significantly improved PDI and water solubility index while preserving nutritional balance. It also enhanced antimicrobial properties, which are desirable for feed storage. Microscopic and structural analyses confirmed good adhesion of the coating. Overall, this study demonstrates a sustainable pathway to convert coastal waste into high-quality aquafeed, offering both environmental benefits and practical value for aquaculture industries.
Keywords: Microencapsulation and Drying Processes; Nanocomposite Films for Food Packaging; Food Drying and Modeling